Analysis of Chemical Laboratory Management at SMAN 55 Jakarta - Amelia Sabella; Hilman Syafei; Umi Habibah; Rahma Rosaliana Saraswati (Risenologi, 2020)
An understanding of laboratory management is highly important to be owned by parties related to the laboratory, both directly and indirectly. Laboratories must be managed and utilized properly, because chemical laboratories are one type of laboratory that is considered quite dangerous in the context of carrying out education, research, and / or community service. This study aims to describe the management of a chemical laboratory using qualitative descriptive research methods. Research subjects were the principal, vice chairman of the curriculum, chair of the laboratory, and teachers in the field of chemistry studies. Data collection techniques are observation, interviews, and documentation. The results of the research are: 1) Planning of chemical laboratory work program has been prepared and standardized by the head of the laboratory, 2) Organizing the laboratory structurally already exists, 3) Organizing by the principal involving all those involved in laboratory management, 4) The implementation of the program is suitable with the plan of the work program, 5) Supervision and evaluation of the principal must still be carried out intensively. In other words, laboratory management at SMA 55 Jakarta has been well organized.